Exploring the Availability and Feasibility of Translanguaging Pedagogy in Kurdish EFL Classrooms: A Descriptive Study - Abubakr, Soma Nawzad; Hussien, Raman Qalandar (Sulaimani Journal for Humanities, 2026)
The aim of this study is to explore whether translanguaging pedagogy is available and possible to be practiced in the Kurdish EFL classrooms at the English Department at the University of Sulaimani. The research’s objective is to obtain insight into teachers' awareness and understanding of translanguaging, and the extent to which it is currently practised in their classrooms. The viewpoints of important stakeholders: teachers, students, and administrators, on translanguaging, are investigated. In addition, the aspects that help or stand as obstacles in implementing translanguaging pedagogy are highlighted. This study uses a mixed-methods approach. The data were collected through semi-structured interviews with teachers and the head of the English Department. In addition, student questionnaires and classroom observations are obtained to analyse the alignment between reported practices and actual classroom behaviour. The study’s findings endeavour to clarify the perspectives and attitudes of all stakeholders toward translanguaging and its practices. The study highlights the need for a rethink of language education policy in Kurdistan. It emphasizes that translanguaging is a possible pedagogical technique that is consistent with the Kurdistan Region’s multilingual reality.
Keywords: Kurdish EFL classrooms; Translanguaging pedagogy; Mixed methods approach; Semi structured interview; Language Attitudes